2021
DOI: 10.30737/ukarst.v5i1.1153
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of DSM By Using Unmanned Aerial Vehicles on the Downstream of Welang Riverbank, District of Pasuruan, Jawa Timur

Abstract: The Digital Surface Model (DSM) is commonly used in studies on flood map modeling. The lack of accurate, high-resolution topography data has hindered flood modeling. The use of the Unmanned Aerial Vehicle (UAV) can help data acquisition with sufficient accuracy. This research aims to provide high-resolution DSM-generated maps by Ground Control Points (GCPs) settings. Improvement of the model's accuracy was pursued by distributing 20 GCPs along the edges of the study area. Agrisoft software was used to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Both are in the order of class 1, with the maximum accuracy of the vertical accuracy test of 0.5m, while the maximum accuracy of the horizontal accuracy test is 0.75m. Previous research regarding the accuracy of DSM using UAV imagery conducted by Khaulan et al (2021) resulted in a CE90 of 1.474m with a map accuracy meeting a scale of 1:5000, while in this study, a CE90 result of was obtained with a map accuracy meeting a scale of 1:2500. The difference in values in previous research is because this research has gone through the process of adding the natural neighbor interpolation method to get better results than before.…”
Section: Dtm Accuracycontrasting
confidence: 43%
See 1 more Smart Citation
“…Both are in the order of class 1, with the maximum accuracy of the vertical accuracy test of 0.5m, while the maximum accuracy of the horizontal accuracy test is 0.75m. Previous research regarding the accuracy of DSM using UAV imagery conducted by Khaulan et al (2021) resulted in a CE90 of 1.474m with a map accuracy meeting a scale of 1:5000, while in this study, a CE90 result of was obtained with a map accuracy meeting a scale of 1:2500. The difference in values in previous research is because this research has gone through the process of adding the natural neighbor interpolation method to get better results than before.…”
Section: Dtm Accuracycontrasting
confidence: 43%
“…Each coordinate and the resulting RMSE value is in Table 1. For DTM, accuracy values based on map scale accuracy (Khaulan et al, 2021), can be seen in Table 2. From the test results on the accuracy above, it can be concluded that the vertical and horizontal accuracy tests of map accuracy meet the 1:2500 scale.…”
Section: Dtm Accuracymentioning
confidence: 99%